2019
DOI: 10.1038/s41386-019-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

β1-adrenergic receptors mediate plasma acyl-ghrelin elevation and depressive-like behavior induced by chronic psychosocial stress

Abstract: The ghrelin system is a key component of the mood and metabolic responses to chronic psychosocial stress. For example, circulating acyl-ghrelin rises in several rodent and human stress models, administered acyl-ghrelin induces antidepressant-like behavioral responses in mice, and mice with deleted ghrelin receptors (GHSRs) exhibit exaggerated depressive-like behaviors, changed eating behaviors, and altered metabolism in response to chronic stress. However, the mechanisms mediating stressinduced rises in ghreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Notably, ghrelin induces cfos expression and increases CRF expression in hypothalamic CRF neurons, induces CRF release from hypothalamic explants, and increases plasma ACTH and epinephrine in rodent and/or human subjects (58)(59)(60)(61)(62)(63). Also relevant, epinephrine and norepinephrine are both potent ghrelin secretagogues, acting via ghrelin cell-expressed β 1 -adrenergic receptors to stimulate ghrelin secretion (30,64). As mentioned, mice with ghrelin cell-selective deletion of β 1 -adrenergic receptors exhibit marked hypoglycemia when exposed to a week-long, severe caloric restriction regimen (30).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ghrelin induces cfos expression and increases CRF expression in hypothalamic CRF neurons, induces CRF release from hypothalamic explants, and increases plasma ACTH and epinephrine in rodent and/or human subjects (58)(59)(60)(61)(62)(63). Also relevant, epinephrine and norepinephrine are both potent ghrelin secretagogues, acting via ghrelin cell-expressed β 1 -adrenergic receptors to stimulate ghrelin secretion (30,64). As mentioned, mice with ghrelin cell-selective deletion of β 1 -adrenergic receptors exhibit marked hypoglycemia when exposed to a week-long, severe caloric restriction regimen (30).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that intra-hippocampal administration of ghrelin fully and intraperitoneal injection partly normalized stressenhanced anxiety-and depression-like phenotypes in a CSDS paradigm (Han et al, 2019). However, another study found that reduced social interaction following CSDS exposure could not be rescued by subcutaneous administration of AG or ghrelin agonist GHRP-2 (Gupta et al, 2019).…”
Section: Role Of Circulating Ghrelin In Fear Anxiety-and Depression-mentioning
confidence: 99%
“…On the other hand, chronic immobilization stress increased plasma AG levels in adrenalectomized rats (Meyer et al, 2014), indicating that stress can drive AG release independently of glucocorticoid production. Interestingly, a recent study demonstrated that elevated AG levels following chronic stress exposure could be reversed by the beta receptor antagonist atenolol (Gupta et al, 2019). This hydrophilic beta receptor antagonist does not readily cross the blood-brain barrier, suggesting that stress-induced elevations in plasma AG may be secondary to activation of the sympathetic nervous system.…”
Section: Ghrelin/ghsr Interactions With the Hpa Axismentioning
confidence: 99%
“…Studies have shown that ghrelin-producing cells express high levels of β1 adrenergic receptors (β1-ARs). Genetic deletion of β1ARs in ghrelin-producing cells or the application of atenolol, a β1-AR-specific antagonist, decreased the plasma levels of both ghrelin and total ghrelin ( Mani et al, 2016 ; Gupta et al, 2019 ), suggesting that the sympathoadrenal system is involved in the regulation of ghrelin production. Meanwhile, it has also been reported that PF might act on peripheral β1-ARs ( Ohta et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to CSDS elicited more severe depressive-like phenotypes in Ghsr -null ( Ghsr –/ – ) mice or hippocampal-specific GHSR1α knockdown mice than in their respective control littermates ( Lutter et al, 2008 ; Han et al, 2019 ). However, some studies have shown that chronic subcutaneous administration of ghrelin and growth hormone-releasing peptide 2, a synthesized agonist of GHSR1α, could not reverse the depressive-like behaviors induced by CSDS ( Gupta et al, 2019 ). Meanwhile, in male rats, the central administration of ghrelin induced depressive-like behaviors during the FST and tail suspension test ( Hansson et al, 2011 ; Jackson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%